Environmental Assessment: Safeguarding nature and accelerating the transition to green energy - Fike, Matej; Pezdevšek, Marko; Roger, Andraž (Journal of Energy Technology, 2026)
The accelerated deployment of a renewable energy infrastructure is a cornerstone of the European green transition, yet the planning, assessment and permitting processes are perceived increasingly as bottlenecks. This paper examines environmental assessment as an enabling framework that can support faster, more coherent and more legitimate decision-making in the context of energy system transformation. Rather than framing environmental assessment as a procedural barrier, the paper conceptualises it as a decision-making and governance infrastructure that integrates environmental, social and health considerations into energy planning. Drawing on recent research and a synthesis of contemporary practice, the paper highlights the importance of early engagement, systems thinking and transformative approaches that move beyond narrow compliance-oriented assessment. Particular attention is given to the balance between acceleration and simplification, as well as to the role of agency, collaboration and professional capacity. The paper concludes that a well-designed environmental assessment does not slow down the green transition, but helps ensure that it is resilient, legitimate and aligned with the long-term sustainability objectives.
Keywords: environmental assessment; green energy transition; Environmental Impact Assessment (EIA); Strategic Environmental Assessment (SEA); sustainable development goals; systems thinking; energy planning and governance